The Use of a “Double-Triple Barrel” Technique during Minimally Invasive Multilevel Tubular Laminectomy. A Technical Note - Roberti, Fabio; Arsenault, Katie Lee (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
This report presents a modified use of multiple tubular retractors (that limits issues related to the sequential redocking of tubular systems) that may prove helpful in cases where a minimally invasive approach is utilized for the treatment of multilevel lumbar stenosis.
Keywords: minimally invasive spine surgery; multilevel laminectomy; tubular retractors